2022
DOI: 10.3390/life12020152
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of the Gut Microbiota in the Physical Growth of Children

Abstract: Gut microbiota succession overlaps with intensive growth in infancy and early childhood. The multitude of functions performed by intestinal microbes, including participation in metabolic, hormonal, and immune pathways, makes the gut bacterial community an important player in cross-talk between intestinal processes and growth. Long-term disturbances in the colonization pattern may affect the growth trajectory, resulting in stunting or wasting. In this review, we summarize the evidence on the mediating role of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 107 publications
0
7
0
1
Order By: Relevance
“…Previous studies suggested that gut microbiota can affect the growth and development of children ( Durda-Masny et al, 2022 ) and pointed maturity of gut microbiome is necessary for long-term expected growth ( Subramanian et al, 2014 ). In our study, the preterm infants were divided into three groups by the LCGMM: the higher BMI group, the lower BMI group, and the BMI catch-up group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that gut microbiota can affect the growth and development of children ( Durda-Masny et al, 2022 ) and pointed maturity of gut microbiome is necessary for long-term expected growth ( Subramanian et al, 2014 ). In our study, the preterm infants were divided into three groups by the LCGMM: the higher BMI group, the lower BMI group, and the BMI catch-up group.…”
Section: Discussionmentioning
confidence: 99%
“…Food security is important as it encompasses both food safety and healthy nutrition of under-5 children. The 2020 Global Report on Food Crises reported that about 135 million people in 55 countries and territories are suffering from acute food insecurity, while 73 million of these figures are from 36 countries in Africa 3 , including Nigeria, with under-5 children mortality rate of 11.7% 5 .…”
Section: Main Textmentioning
confidence: 99%
“…Food preparation plays an important role in improving appearance, digestibility, and flavor, extending shelf-life, destruction of microbes, and oxidative enzymatic reaction. Researchers agreed that there are two methods of food preparation, which include pre-preparation and preparation 1 , 3 5 . Pre-preparation methods are activities by which food is prepared for cooking, such as cleaning, peeling, grating, sieving, grinding, blanching, and washing.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Mikrobiota pada usus sendiri merupakan perantara penting dalam mekanisme penghasil energi, penyimpanan lemak, berperan dalam regulasi metabolisme lipid dan glukosa, induksi peradangan tingkat rendah, fungsi penghalang usus dari mikrobiota patogen, kontrol rasa kenyang melalui hormon usus. Mikrobiota berkontribusi pada aktivitas asam lemak rantai pendek (SCFA) dan e-ISSN: 28 .…”
Section: Jenis Dan Komposisi Mikrobiota Pada Anak Stunting Dan Normalunclassified